The role of interpersonal justice perceptions of employees during major organisational change due to a merger and acquisition - Walters, Chrizelda; Vos, H. D. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA)--University of Stellenbosch, 2005.